Chronic urticaria in the real‐life clinical practice setting in the UK: results from the noninterventional multicentre AWARE study. (26th August 2020) - Savic, S.; Leeman, L.; El‐Shanawany, T.; Ellis, R.; Gach, J.E.; Marinho, S.; Wahie, S.; Sargur, R.; Bewley, A.P.; Nakonechna, A.; Randall, R.; Fragkas, N.; et al.
Summary: Background: Chronic urticaria (CU) is a skin condition characterized by repeated occurrence of itchy weals and/or angio‐oedema for > 6 weeks. Aim: To provide data demonstrating the real‐life burden of CU in the UK. Methods: This UK subset of the worldwide, prospective, noninterventional AWARE study included patients aged 18–75 years diagnosed with H1‐antihistamine (H1‐AH)‐refractory chronic spontaneous urticaria (CSU) for > 2 months. Baseline characteristics, disease activity, treatments, comorbidities and healthcare resource use were documented. Quality of life (QoL), work productivity and activity impairment were assessed. Results: Baseline analysis included 252 UK patients. Mean age and body mass index were 45.0 years and 29.0 kg/m 2, respectively. Most patients were female (77.8%) and had moderate/severe disease activity (mean Urticaria Activity Score over 7 days was 18.4) and a 'spontaneous' component to their CU (73.4% CSU; 24.6% CSU and chronic inducible urticaria). Common comorbidities included depression/anxiety (24.6%), asthma (23.8%) and allergic rhinitis (12.7%). A previous treatment was recorded for 57.9% of patients. Mean Dermatology Life Quality Index score was 9.5, and patients reported impairments in work productivity and activity. Healthcare resource use was high. Severity of CSU was associated with female sex, obesity, anxiety and diagnosis. Only 28.5% of patients completed all nine study visits, limiting analysis of long‐term treatment patterns and disease impact. Conclusions: Adult H1‐AH‐refractory patients with CU in the UK reported high rates of healthcare resource use and impairment in QoL, work productivity and activity at baseline. The differing structures of UK healthcare may explain the high study discontinuation rates versus other countries.